Faith, Finance, and Economy Beliefs and Economic Well-Being - Akram, Tanweer; Rashid, Salim (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This open access book seeks to foster a multidisciplinary understanding of the ties between faith, financial intermediation, and economic progress by drawing on research across economics, finance, history, philosophy, ethics, theology, public policy, law, and other disciplines. Chapters in this edited volume examine themes as consequential as economic opportunities, real world outcomes and faith; values and consumerism; faith, financial intermediation and economic development in Western and Islamic societies; and the impact of faith issues on US workers, on the workplace and religion, and on the characteristics of good wealth. Though engaging with difficult questions, this book is written in an accessible style to be enjoyed by laypeople and scholars alike.